2001
DOI: 10.1177/107906320101300202
|View full text |Cite
|
Sign up to set email alerts
|

Calculating Number of Offenses and Victims of Juvenile Sexual Offending: The Role of Posttreatment Disclosures

Abstract: This research was designed to compare data obtained from agency records at three treatment programs for juvenile male sex offenders with information available from clinicians once youth and their families had been in treatment for at least 6 months. Results revealed that over the course of treatment, youth and their families disclosed information about additional victims and offenses, physical and sexual abuse of the offenders, and several aspects of a violent and sexualized family environment. Over half the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…Third, it is certainly possible that there are variables besides those examined in the present study that distinguish between juvenile sexual offenders and nonsexual offenders. For example, there is some evidence that exposure to pornography (e.g., Ford & Linney, 1995) or domestic violence (e.g., Baker, Tabacoff, Tornusciolo, & Eisenstadt, 2001) may be relatively common among juvenile sexual offenders. It would be worth directly examining such variables in a study with comparison groups like those in the present study.…”
Section: Discussionmentioning
confidence: 98%
“…Third, it is certainly possible that there are variables besides those examined in the present study that distinguish between juvenile sexual offenders and nonsexual offenders. For example, there is some evidence that exposure to pornography (e.g., Ford & Linney, 1995) or domestic violence (e.g., Baker, Tabacoff, Tornusciolo, & Eisenstadt, 2001) may be relatively common among juvenile sexual offenders. It would be worth directly examining such variables in a study with comparison groups like those in the present study.…”
Section: Discussionmentioning
confidence: 98%
“…An examination of the case records of the youth misclassified revealed that they were offenders with no evidence in their records of family deceptions. As previous research has demonstrated (Baker et al, 2001), agency records may underreport certain aspects of family experiences. This has been found to be true for families of sex offenders, whose records significantly underreport aspects of a sexualized family environment.…”
Section: Discussionmentioning
confidence: 91%
“…Data regarding family secrecy obtained from the Family Deception Measure (FDM), created specifically for this study by the researchers at the three participating agencies. All other data were obtained the Youth Characteristics Measure (YCM) also created by the senior researchers and described in detail elsewhere (Baker et al; 2001). In brief, the YCM was designed to allow researchers to gather data from confidential agency records compiled at the time youth entered treatment.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations